1997
DOI: 10.1097/00005537-199710000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Management of Nasopharyngeal and Oropharyngeal Stenosis in Children

Abstract: Nasopharyngeal stenosis and oropharyngeal stenosis are rare and challenging problems in the pediatric population. The most common etiology is currently the surgical trauma associated with adenotonsillectomy. Stenosis can vary from a thin band to a complete obstructing cicatrix. Presenting symptoms range from mild hyponasal speech to severe airway obstruction. We present a series of eight children with varying degrees of stenosis and associated symptoms. Choice of treatment varied with the severity of disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 21 publications
0
52
0
Order By: Relevance
“…However, in the past, it was mostly due to complications of infectious diseases, such as rhinoscleroma, diphtheria, syphilis and tuberculosis [1,3]. In childhood, NPS can also be observed after adenotonsillectomy, but the incidence of this complication in both adults and children is very rare [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the past, it was mostly due to complications of infectious diseases, such as rhinoscleroma, diphtheria, syphilis and tuberculosis [1,3]. In childhood, NPS can also be observed after adenotonsillectomy, but the incidence of this complication in both adults and children is very rare [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Careful operative technique, judicious use of electrocautery, and adequate pre-operative evaluation for adenoidectomy, or uvulopalatoplasty during the primary surgery are essential to prevent nasopharyngeal stenosis. In cases of mild scarring, McLaughlin et al [5] found some success with triamcinolone acetonide injections, but the only curative treatments for acquired nasopharyngeal stenosis are surgical [5]. Clinically, the severity of symptoms is closely related to the degree of stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Each case must be individualized because the location, extent, and severity vary widely. Less invasive treatment options described include local steroid injection [5], adhesion lysis by laser, topical mitomycin application, and nasopharyngeal obturator placement [6]. More extensive procedures include flap takedown in cases of pharyngoplasty for velopharyngeal insufficiency, and reconstruction using local, regional, or vascularised flaps [1,5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Nasopharyngeal stenosis is a rare condition and is classified according to the etiology, into primary nasopharyngeal stenosis (due to a disease process as syphilis) or secondary nasopharyngeal stenosis (postoperative). However, most current cases are understood to be secondary to adenotonsillectomy, uvulopalatoplasty, or radiotherapy for nasopharyngeal carcinoma [3,4]. The potential complication of nasopharyngeal stenosis after surgery is due to technical errors (as excessive excision of posterior tonsillar pillars, undermining the posterior pharyngeal wall, and excessive electrocautery), and postoperative wound complications as dehiscence, infection, necrosis or excessive scarring in keloid-forming patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many treatment modalities are being tried to cure this problem. In cases of mild scarring, McLaughlin et al found some success with triamcinolone acetonide injections [4]. Local injection of corticosteroids has been shown to reduce the secretion of collagen as well as leading to its solubilization, significantly reducing the occurrence of keloids [9].…”
Section: Introductionmentioning
confidence: 99%